Criminal and legal characteristic of forced and/or the unlawful removal of human organs and tissues for transplants under the legislation of the Republic of Kazakhstan - Balgimbekov, D.U.; Seitkhozhin, B.U.; Koszhanov, А.S. (KSU Publ., 2016)
The article gives a criminal and legal characteristic of the forced and/or unlawful removal of human organs or tissue for transplants, which is criminalized under article 116 of the Criminal Code of the Republic of Kazakhstan dated 3 July 2014. The valuable comments and suggestions provided by the experts and the official national crime statistics were compiled. This offense refers to the formal composition in the current amendment. This is not entirely appropriate, because the harm is done to the victim's health. In order to address this gap in article 116, Part 2, of the Criminal Code of the Republic of Kazakhstan should be provided socially dangerous consequences, in the form of causing serious injury to health.
Қазақстан Республикасының заңнамасы бойынша адамның ағзалары мен тiндерiн алып қоюға мəжбүрлеу немесе заңсыз алып қоюдың қылмыстық-құқықтық сипаттамасы
Уголовно-правовая характеристика принуждения к изъятию или незаконное изъятие органов и тканей человека по законодательству Республики Казахстан
Keywords: transplantation; coercion; unlawful removal; human organs and tissues; organ transplantations; donation